THE EFFECT OF AI-BASED MULTIMEDIA INTEGRATED PROJECT-BASED LEARNING ON STUDENTS’ COLLABORATION SKILLS AND CONCEPTUAL UNDERSTANDING IN THE PERIODIC TABLE - Resa Sarita Gerungan; Jaslin Ikhsan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aimed to investigate the effect of AI-based multimedia integrated Project-Based Learning (PjBL) on students’ collaboration skills and conceptual understanding in learning the Periodic Table. The study employed a quantitative approach using a quasi-experimental method with a non-equivalent control group pretest–posttest design. The participants consisted of 64 tenth-grade students at Universitas Negeri Yogyakarta, divided into an experimental group and a control group, with 32 students in each class. The experimental group was taught using AI-based multimedia integrated PjBL, while the control group received cooperative learning instruction. Data were collected using a collaboration skills questionnaire and a conceptual understanding test. The data were analyzed using MANOVA, Independent Sample t-Test, N-Gain analysis, and Partial Eta Squared effect size analysis with the assistance of SPSS 25. The results showed significant simultaneous differences between the experimental and control groups after treatment, as indicated by the MANOVA test (p = 0.005 < 0.05). The Independent Sample t-Test also revealed significant differences in collaboration skills (p = 0.016) and conceptual understanding (p = 0.008). The N-Gain analysis indicated that the experimental group achieved higher improvement in collaboration skills (0.478) and conceptual understanding (0.393) compared to the control group. Furthermore, the effect size analysis showed medium effects on collaboration skills (η² = 0.090) and conceptual understanding (η² = 0.108). Therefore, AI-based multimedia integrated Project-Based Learning was found to be effective in improving students’ collaboration skills and conceptual understanding in chemistry learning, particularly on the Periodic Table topic.